2002
DOI: 10.1152/ajplung.00202.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increased expansion of the lung stimulates calmodulin 2 expression in fetal sheep

Abstract: Obstruction of the fetal trachea causes the lungs to expand with accumulated liquid. Although this is a potent stimulus for lung growth, the mechanisms involved are unknown. Our aim was to identify genes that are differentially expressed as a result of increased fetal lung expansion. Using differential display RT-PCR, we isolated a cDNA fragment partially encoding calmodulin 2 (CALM2) and identified the remainder of the coding region by 5′-rapid amplification of cDNA ends. Differential expression of CALM2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Thereby, POV would cause a reduction of the post-toprecapillary resistance ratio and decrease the capillary hy-14 14 Control AVP drostatic pressure. This hypothesis, however, needs to be verified in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, POV would cause a reduction of the post-toprecapillary resistance ratio and decrease the capillary hy-14 14 Control AVP drostatic pressure. This hypothesis, however, needs to be verified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A Shiley tube (inner diameter 10 mm; Tyco Healthcare Group, Pleasanton, CA) was used for tracheostomy and a Dover catheter (12)(13)(14) Fr; Sherwood Medical, St Louis, MO) for urinary bladder catheterization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-Nitrotyrosine protein expression in lung tissue was determined using anti-3-nitrotyrosine monoclonal antibody (Cayman Chemicals, Ann Arbor, MI; Catalog No. 10006966) with streptavidin secondary antibody as described previously (20). Myeloperoxidase activity was determined using a commercially available assay (Myeloperoxidase Activity Assay, Northwest Life Science Specialties, Vancouver, Canada) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The TROP2 protein is a cell surface glycoprotein receptor (21) that, when stimulated, increases intracellular calcium levels (53). An increase in intracellular calcium is an important mediator of normal and stretch-induced lung growth (23,39,50). Numerous studies have demonstrated that TROP2 promotes cell proliferation in tumor cells (13) and is involved in the formation, growth, and metastasis of tumors (19,30,37,51,55).…”
mentioning
confidence: 99%